Pelatihan Pengelolaan Emosi bagi Orang Tua untuk Meningkatkan Hubungan Keluarga yang Harmonis - Ruminta Simamora (Cattleya Darmaya Fortuna, 2024)
Emotion management training for parents has an important role in strengthening harmonious family relationships, especially in supporting effective parenting. This study aims to evaluate the impact of training on parents' ability to manage emotions and improve communication patterns in the family. The training program was conducted over three days and involved 50 parents as participants. Data were collected through pre-test, post-test, observation, and in-depth interviews. Results showed a significant improvement in emotion management skills, with the average score increasing from 65.2 to 84.7 (100 scale). In addition, 78% of participants reported better ability to control emotions, and 85% felt more confident using assertive communication techniques. The program also created positive changes in the family atmosphere, such as a decrease in verbal conflict and an increase in more harmonious relationships. Despite challenges such as time constraints and differences in participants' backgrounds, the training had a significant positive impact. The program is recommended to be implemented in other communities with follow-up support to sustain its impact..